PERSEPSI MAHASISWA TENTANG KETIDAK-JUJURANAKADEMIK: STUDI KASUS MAHASISWA PROGRAM VOKASI UNIVERSITAS INDONESIA - Yuliyanto, Heri (Jurnal Vokasi Indonesia, 2015)
Often we see students gathered tasks given by the lecturers and they are copying answers between students and others. They perform this action with no load, even though the task is an individual task. Do they know that what they are doing is an action that is contrary to the basic values of academic integrity. Or perhaps they are not aware that they are not a violation, since they merely imitate or follow the habits of seniors or friends the same age. Then comes the question "How do they (students) do dishonesty (cheating)?" And "Why are or what background they commit acts of academic dishonesty?" Based on the analysis of primary data obtained by distributing a questionnaire to students vocational program UI, and secondary data obtained from the data of students who cheat (academic violations), namely cheating Even during the period 2012/2013 to 2014/2015 Odd and continued to look at student biographical data and results academic evaluation found that women students are proportionally larger than the act of cheating men , furthermore student selection process through SIMAK UI has a proportionally larger than the students that the selection process through PPKB.